(untitled) (REMUNOM, 2025)
Buildings have been built for millennia using various techniques, with the project being an essential item for planning, execution and cost assessment. New technologies such as the BIM Methodology (Building Information Modeling) have arrived at the construction site, seeking to improve quality, minimize costs, meet deadlines, among others. The compatibility of projects contributes to the development and modernization of the civil construction sector. To this end, this bibliographical research of an exploratory nature is presented. The general objective of this study is to demonstrate the differences between the use of the traditional system and the BIM system by Civil Engineering offices. Regarding the specific objectives, we have the following: investigate the benefits of well-executed compatibility; list the requirements necessary to identify priority projects. As a result, it can be pointed out that Brazil has advanced in this regard and its professionals have presented very relevant solutions in order to maintain development in the civil construction sector coupled with the dictates of society in terms of quality, reduction of rework and integration between subjects and teams involved in civil construction.